Weather Implication for Dengue Fever in Jakarta, Indonesia 2008-2016 - ., Hasanah; Susanna, D (KnE Life Sciences, 2019)
Dengue Fever is an endemic disease that occurs throughout the year. It is caused by the dengue virus and is transmitted by mosquitoes, especially Aedes aegypti. Weather factors such as temperature, rainfall, and humidity are the optimal conditions for mosquitoes to breed. The purpose of this research is to know the relationship of dengue fever with weathers factors (temperature, rainfall, and humidity) in Daerah Khusus Ibukota (DKI) Jakarta in 2008-2016. This research is descriptive with ecological study design. The data source is secondary data from DKI Jakarta Health Office for Dengue Hemorrhagic Fever case and Jakarta Central Bureau of Statistics for climate data. Correlation test is used to know the strength and direction of the relationship between independent variable and dependent variable. The results show a significant relationship between weather variables that have been studied; temperature (p-value <0.05, r = -0.264), rainfall (p-value <0.05, r = 0.210), and humidity (p-value <0.05, r = 0.504); and dengue fever cases in DKI Jakarta in 2008-2016. In conclusion, there are two weather variables that have a positive correlation to dengue fever cases; they are rainfall and humidity. While the temperature has a negative correlation. The highest correlation to dengue fever cases is humidity it is strong. While others such as temperature and rainfall are in the category of moderate and weak correlation, respectively. Keywords: Dengue fever, temperature, rainfall, and humidity